ANALISIS PEMETAAN STATUS PENGEMBANGAN EKONOMI LOKAL (PEL) DI KABUPATEN SUKOHARJO - ADI, R. KUNTO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Local Economic Development (LED) revitalization objective to change view ofstockholders included of Central Government, Regional Government, Non Government Institution, and community, for Local Economic Development (LED) to be instrument of developing economic activity was based on locally resources for increasing the sustainable of local community welfare.